Bioethanol – What Has Brazil Learned About Yeasts Inhabiting the Ethanol Production Processes from Sugar Cane? - Andrietta, Maria da Graça Stupiello; Andrietta, Sílvio Roberto; Stupiello, Érika Nogueira Andrade (IntechOpen, 2011)
None